Significant Other Staging the American in China - Conceison, Claire (University of Hawaii Press, 2004)
Chinese views of the United States have shifted dramatically since the 1980s, with changes in foreign relations, increased travel of Chinese citizens to the U.S., and wide circulation of American popular culture in China. Significant Other explores representations of Americans that emerged onstage in China between 1987 and 2002 and considers how they function as racial and cultural stereotypes, political strategy, and artistic innovation. Based on fieldwork in Beijing and Shanghai, it offers a unique view of contemporary Mainland Chinese spoken drama from the perspective of a Western academic who is both a Chinese studies scholar and a theatre practitioner. Claire Conceison's close readings of recent plays take into account not only the texts of the plays themselves and other primary sources, but also production contexts, creative origins, artistic collaboration, and audience reception. Identifying the American as China's "significant Other," Conceison introduces the complex cultural relationship between China and the United States, situating it in both the long history of Sino-Western relations and the present dynamics of post-colonialism. She then examines the emergent discourse of Occidentalism, tracing its origins and recent circulation and repositioning it as a discursive strategy to analyze appearances of Americans on the Chinese stage. Conceison maintains that Chinese staging of American characters-often played by local actors made up and costumed as Americans, and more recently played by foreigners themselves-reveals cultural norms and attitudes regarding the United States, reflects Sino-American political relations, articulates Chinese national and cultural identity, and signifies innovation in spoken drama as an art form
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Jul 2021)
Keywords: SOCIAL SCIENCE / Ethnic Studies / Asian American Studies